Circadian rhythmicity of body temperature and metabolism - Refinetti, R. (Temperature, 2020)
This article reviews the literature on the circadian rhythms of body temperature and whole-organism metabolism. The two rhythms are first described separately, each description preceded by a review of research methods. Both rhythms are generated endogenously but can be affected by exogenous factors. The relationship between the two rhythms is discussed next. In endothermic animals, modulation of metabolic activity can affect body temperature, but the rhythm of body temperature is not a mere side effect of the rhythm of metabolic thermogenesis associated with general activity. The circadian system modulates metabolic heat production to generate the body temperature rhythm, which challenges homeothermy but does not abolish it. Individual cells do not regulate their own temperature, but the relationship between circadian rhythms and metabolism at the cellular level is also discussed. Metabolism is both an output of and an input to the circadian clock, meaning that circadian rhythmicity and metabolism are intertwined in the cell.